The Role of Meaning Competence And Self-Determination In Mediating The Effect Of Digital Transformation On The Job Performance Of Employees At The BPJS Health Office In Cirebon City - Amaliah, nurmala; wibowo, sandi nasrudin (Jurnal Manajemen, 2026)
Digital transformation has become a crucial factor in improving employee performance; however, its success is not only determined by technological aspects, but also by the psychological readiness of employees. This study aims to analyze the effect of digital transformation on work performance, with meaning competence and self-autonomy as mediating variables among employees of the Cirebon BPJS Health Office. This study uses an associative quantitative approach with a saturated sampling technique involving 109 respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results show that digital transformation has a significant positive effect on work performance, meaningfulness, and self-autonomy. In addition, meaningful competence and self-autonomy significantly influence work performance. Mediation analysis shows that digital transformation acts as a mediator in the relationship between meaningful competence and autonomy and work performance. These findings highlight that the success of digital transformation in improving work performance is greatly influenced by employees’ ability to find meaning in their work and their level of autonomy and intrinsic motivation.